Understanding processing, maturity and harvest period effects to authenticate early-spring Longjing tea using stable isotopes and chemometric analyses. (June 2021) - Xia, Wei; Li, Zuguang; Yu, ChongChong; Liu, Zhi; Nie, Jing; Li, Chunlin; Shao, Shengzhi; Zhang, Yongzhi; Rogers, Karyne M.; Yuan, Yuwei
Abstract: Low-yielding early-spring (ES) Longjing tea is popular with Chinese consumers and commands a high price due to its scarcity, but it has a heightened risk of substitution with lower value tea products from later harvest periods due to similarities in appearance. In this study, tea samples from different harvest periods were analyzed using stable isotope analyses ( δ 13 C, δ 15 N, δ 2 H, and δ 18 O) to distinguish effects from different tea drying processes, leaf maturity and harvest period. Our results showed there were no significant differences among all stable isotopes for different tea drying processes ( p  > 0.05). δ 13 C values showed little difference among different maturity tea leaves over the entire spring period ( p  > 0.05). δ 15 N values of mature leaves were found to be 0.4 ‰ higher than young leaves in early spring. δ 2 H and δ 18 O values of different maturity leaves had different fractionation ratios (RM/Y ) of 1.17 and 1.14 in early spring and late spring, respectively ( p  < 0.05). Generally, tea stable isotopes showed seasonal enrichment in early spring, then depletion in late spring. δ 18 O values were significantly correlated to air humidity, light intensity and precipitation (0.53 < r < 0.92), and δ 13 C and δ 2 H values were negatively correlated with air temperature and air humility, respectively (0.57 < r < 0.74). A supervised chemometric model (orthogonal partial least squares discriminant analysis, OPLS-DA) was used to classify the ES and late-spring (LS) Longjing tea, and the discriminant accuracy of the training set was 95 %, while the test set and blind set showed a good accuracy of 100 % and 83.3 %, respectively. Result showed that this new method was a feasible technique to protect ES Longjing tea, and also provides evidence that tea harvest periods can be predicted by using stable isotopes and chemometric analyses. Highlights: No significant isotope differences found with different drying methods of tea. Stable isotopes revealed differences in young and mature tea leaves. High correlation between stable isotopes in tea and climate, especially δ 18 O. Isotopes and OPLS-DA discriminated early-spring Longjing tea from later harvests.